El ejercicio de la potestad sancionadora administrativa y su implicación en el principio de imparcialidad como garantía del procedimiento - Llinguin Sampedro, Juan Pablo (2024)
SUMMARY The title of this investigation is “The exercise of the administrative sanctioning power and its implication in the principle of impartiality as a guarantee of the procedure”, which is based on the Organic Administrative Code, referring to the division of the instructing body and the sanctioning body, the same as It must be mandatory in each of the public institutions of the State. In this way, the purpose of this investigation is the study of the administrative sanctioning power and the principle of impartiality as a guarantee of the procedure. The methodological design appropriate to a social legal investigation, through the inductive, legal - analytical, dogmatic, legal-doctrinal, legal - descriptive, legal - correlational method and case study method; quantitative and qualitative research approach; types of pure, dogmatic, exploratory legal, correlational legal and descriptive legal research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, which has made it possible to draw conclusions and recommendations according to the problem investigated, generally considering that there is a lack of separation of functions in the National Agency for Regulation, Control and Surveillance. Health and the Quality Assurance Agency for Health Services and Prepaid Medicine, that is, the provisions of article 248 paragraph 1 of the Organic Administrative Code are not complied with in accordance with article 76 paragraph 7 literal k of the Constitution of the Republic of Ecuador. KEYWORDS: sanctioning power, investigative body, sanctioning body, impartiality, sanctioning procedure, due process, violation, nullity